If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 33 + 3y + -12 = 12y + -9 + -4y Reorder the terms: 33 + -12 + 3y = 12y + -9 + -4y Combine like terms: 33 + -12 = 21 21 + 3y = 12y + -9 + -4y Reorder the terms: 21 + 3y = -9 + 12y + -4y Combine like terms: 12y + -4y = 8y 21 + 3y = -9 + 8y Solving 21 + 3y = -9 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 21 + 3y + -8y = -9 + 8y + -8y Combine like terms: 3y + -8y = -5y 21 + -5y = -9 + 8y + -8y Combine like terms: 8y + -8y = 0 21 + -5y = -9 + 0 21 + -5y = -9 Add '-21' to each side of the equation. 21 + -21 + -5y = -9 + -21 Combine like terms: 21 + -21 = 0 0 + -5y = -9 + -21 -5y = -9 + -21 Combine like terms: -9 + -21 = -30 -5y = -30 Divide each side by '-5'. y = 6 Simplifying y = 6
| -1y-22-1y=-16 | | 15=-3(n-4) | | x^2+26x+112=0 | | x+20+4x=-33-4x-37 | | 6x-6=10x+15-15 | | 5-(3)= | | 48f+6.4=-8.48 | | 10y+9=-3 | | 2(-2x+4)=8 | | -4(2x-3)-3-8x=-11 | | 24-6k=6[4-k] | | 10+45u= | | a+140=a+0.05a | | 15-6x+7-3x= | | -16+6=-6r+2 | | 10x-3y=24 | | 2(5+3)= | | 4x+28=6x+2 | | x^2+14x-18=10x+3 | | 1.6+y=-7.3 | | 5(x-2)=8+5x | | 4a+12=3a+15 | | 4y+-53+6=51 | | -3x=-2(x+6) | | 13+45x=13+5x | | 4-12x+5x=9-2x | | 3(3x-2)=16 | | 24.75+6s=2(15.60)+3s | | 5n+4=7n+7-2n | | -g+6+g=-4g+4 | | -4(7y+9)=3(3-5y)-4y | | nm+7p=8 |